2015
DOI: 10.1016/j.ijrobp.2015.07.257
|View full text |Cite
|
Sign up to set email alerts
|

Modern Radiation Therapy and Cardiac Outcomes in Breast Cancer

Abstract: International Journal of biology physics www.redjournal.org decrement. The results of the present study could help physicians better stratify patients for aggressive cardioprotective techniques. mortality with a subdistribution hazard ratio of 2.02 (95% CI 1. 23-3.34). No other outcome, including cardiac mortality for the entire cohort, showed a significant relationship with tumor laterality. Conclusions: For women with a history of cardiac disease, those with left-sided breast cancer who underwent radiation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 26 publications
1
25
0
2
Order By: Relevance
“…Adjuvant radiotherapy for breast cancer reduces the risk of locoregional recurrence as well as breast cancer death . However, some radiation is inevitably delivered to normal tissue, such as the heart and lungs, which has been shown to increase the risk of cardiovascular and pulmonary disease . Darby et al have shown that the relative risk of ischemic heart disease increases with 7.4% per Gy increased mean heart dose, with no apparent threshold.…”
Section: Introductionmentioning
confidence: 99%
“…Adjuvant radiotherapy for breast cancer reduces the risk of locoregional recurrence as well as breast cancer death . However, some radiation is inevitably delivered to normal tissue, such as the heart and lungs, which has been shown to increase the risk of cardiovascular and pulmonary disease . Darby et al have shown that the relative risk of ischemic heart disease increases with 7.4% per Gy increased mean heart dose, with no apparent threshold.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, a Surveillance, Epidemiology and End Results Program (SEER) database study of 29 102 patients diagnosed with breast cancer from 2000 to 2009 showed a small increase in the risk of percutaneous coronary intervention (PCI) after radiation therapy: 5.5% versus 4.5% for left-sided breast cancer versus right-sided breast cancer. In those who underwent PCI, left-sided breast cancer carried significantly increased risk of cardiac mortality with a subdistribution HR of 2.02 (95% CI 1.23 to 3.34), compared with right-sided breast cancer 62. Of note, prior studies have shown right-sided breast cancer also carries significantly increased but smaller risk of cardiovascular events compared with left-sided breast cancer 57.…”
Section: Discussionmentioning
confidence: 92%
“…They found that the rate of major coronary events increased by 7.4% per Gy without an apparent threshold, and the major coronary events included myocardial infarction, coronary revascularization, and death from ischemic heart disease [13,19]. Even in the era of modern RT, in comparison with patients with right-sided breast cancer, those with left-sided breast cancer experienced a small increase in the risk of percutaneous coronary intervention (PCI) following RT, and the 10-year cumulative incidences in patients with leftsided and right-sided disease were 5.5 and 4.5%, respectively [20].…”
Section: Epidemiological Data For Radiation-related Heart Diseasementioning
confidence: 99%